Hepatolenticular degeneration with depressive episodes of bipolar disorder： a case report - Xiang Wei; Chen Yan (Sichuan jingshen weisheng, 2024)
This case reported a 17-year-old female patient who presented to the hospital with "poor mood and irritability for more than 5 months". The patient was diagnosed with hepatolenticular degeneration at the age of five. According to the International Classification of Diseases， tenth edition （ICD-10）， she was diagnosed with hepatolenticular and depressive episodes of bipolar disorder. The condition improved after administration of a combination of a mood stabilizer and an antidepressant. There are few reports of hepatolenticular degeneration combined with depressive episodes of bipolar disorder， and it is controversial whether the diagnosis should be considered a psychiatric disorder due to a physical illness or a co-morbidity. In addition， somatic conditions are often overlooked in the treatment of patients with psychiatric disorders. This case analyzed the diagnosis and medication by integrating the patient's psychiatric symptoms and somatic conditions， suggesting that psychiatrists should pay attention to both psychiatric symptoms and the patient's previous history of somatic diseases in their clinical work for rational diagnosis and treatment.